Evaluation of the Spectrophotometric Determination of Zinc with Methylene Blue and Thiocyanate - Isjrin Noerdin (Journal of Mathematical and Fundamental Sciences, 1965)
Abstract. The reaction of zinc with methylene blue and thiocyanate is developed to a highly sensitive spectrophotometric  determination of zinc in which the unknown zinc is reacted with methylene blue and thicyanate, giving insoluble complex. This is filtered off and the decrease in the amount of zinc present, is measured. Suitable masking agents prevent interference of most common ions, even when present in large amounts, except with cobalt, copper, cadmium and mercury which do not interfere if present in small amounts only. In simplicity, sensitivity and freedom from interference this method compares favorably with dithizone and zincon methods.Ichtisar. Reaksi seng dengan biru metilena dan tiosianat diperkembangkan mendjadi suatu penentuan spektrofotometris jang sangat pekak untuk seng dalam mana seng itu direaksikan dengan biru metilena dan tiosianat dengan menghasilkan suatu kompleks jang tak larut. Kompleks ini disaring dan berkurangnja djumlah seng diukur.  Dengan zat penkompleks jang sesuai dapat dihilangkan gangguan dari kebanjakan ion jang umum terdapat walaupun djumlahnja besar, ketjuali untuk Cobalt, tembaga dan raksa, ion2 mana hanja tidak akan mengganggu kalau djumlahnja ketjil. Ditilik dari segi kesederhanaan, kepekaan dan kebebasan dari gangguan tjara ini menguntungkan djika dibandingkan dengan tjara2 detbezon dan zincon.